The potential of green mussel shells (Perna viridis) as an alternative calcium source in the cement industry - Herliati Rahman; Firda Fitriani; Seventien Wahyu Hendry K (Sustinere: Journal of Environment and Sustainability, 2024)
Green mussel shells (GMSs) are a potential source of calcium oxide for the cement industry. As the largest producer of shells in Asia, Indonesia generates an annual production of 309,886 tons, with approximately 70% of this comprising shell waste. Addressing this issue is crucial to reducing environmental pollution and fistering innovation in eco-friendly cement production. This study aims to explores the extraction of calcium carbonate (CaCO3) from GMSs through a 4-hour calcination process at temperatures of 700°C, 800°C, and 900°C. Analytical methods, including titrimetric analysis and X-ray fluorescence revealed that GMS flour contains 98.16% calcium oxide (CaO). X-ray diffraction analysis at 900°C identified CaCO3 phases consistent with ICDD data No. 01-070-9854, with diffraction peaks observed at 2θ values of 29.4°, 32.21°, and 37.37° (100%). Compressive strength tests further demonstrated that incorporating 10% GMS-derived material into cement increases its compressive strength by 2.3%. These findings highlight the potential of GMSs as an alternative raw material for the cement industry. Maximizing shell waste utilization not only mitigates environmental impact but also supports more sustainable and environmentally friendly cement production. This approach represents a significant advancement in waste management innovation and the development of green solutions in the construction sector.